Case Report: 18F-PSMA-1007 PET/CT Avid Solitary Penile Metastasis of Castration-Resistant Prostate Cancer With a PSA of 0.072 ng/ml - Li, Yongliang; Li, Yanmei; Dong, Siying; Chen, Jian; Yang, Pengfei; Li, Juan (Frontiers in Oncology, 2022)
Penile metastasis of prostate cancer is rare, with a poor prognosis, and only a limited number of relevant cases have been reported so far. With the application of 18F-PSMA-1007 PET/CT, the biochemical recurrence of prostate cancer can be detected at an early stage for providing important evidence, facilitating clinical decision making. Here, we have reported a case of solitary penile metastatic recurrence in the context of mild PSA progression (PSA: 0.072 ng/mL). This case highlights the preferable sensitivity of 18F-PSMA-1007 PET/CT imaging in prostate cancer.